Chemical Constituents of the Essential Oils of Cinnamomum sinrok, Blume - Jantan, Ibrahim; Mohd Ali, Nor Azah; Ahmad, Abdul Rashih; Ahmad, Abu Said (Universiti Putra Malaysia Press, 1994)
The leaf, bark and wood oils of Cinnamomum sintok were isolated in 0.87, 1.63 and 0.29% yields, respectively, by water distillation. The components of the oils were identified by co-chromatography with authentic samples on two different capillary columns, Kovats retention index and gas chromatographic-mass spectrometric(GC-MS) analysis. Sesquiterpenoids accounted for more than 80% of the oil. However, the most abundant component was linalool which constituted 17.4% of the oil. The constituents of the bark and wood oils were similar, but the concentrations differed. The major component of the bark and wood oils was eugenol which constituted 87.5 and 72.6% of the oils respectively.